Dwelling in the World with People of Peace: Missional Discipleship within the Missio Dei - Ladd, Nick (Ecclesial Futures, 2021)
Dwelling in the World is a practice designed to help churches to form a public shared identity in the mission of God with people in their wider communities who want to work with them—their “people of peace”. Grounded in the missio Dei, this practice offers a concrete example of missional discipleship. How does this work in practice? And what happens between church members and their people of peace? Based on research conducted in 2020, this article presents that research and its findings, paying close attention to the lived experience of those involved. It argues that an exchange takes place which is relational rather than transactional where the partners are drawn together into the life of God as they join together in God’s mission. This is a disturbing and transforming public journey, which decentres discipleship from the private, individualised world of church and, by means of attention to the “other,” re-centres it in God and God’s agency in mission. Therefore the outcome may be appropriately named as missional discipleship.